Ovary peltate trichomes of Zeyheria montana (Bignoniaceae): Developmental ultrastructure and secretion in relation to function - Machado, SR; Gregorio, E. A.; Guimaraes, E. (Oxford University Press, 2006)
center dot Background and Aims Nectar production in the Bignoniaceae species lacking a nectariferous functional disc is ascribed to trichomatic glands around the ovary base and/or on the inner corolla wall. Nevertheless, knowledge about the secretion and function of these glands is very incomplete. The purpose of this paper is to study, from a developmental viewpoint, the ultrastructure, histochemistry and secretory process of the peltate trichomes on the ovary of Zeyheria montana, a species in the Bignoniaceae which has a rudimentary disc.center dot Methods Samples of the gynoecium at various developmental stages were fixed and processed for light and electron microscopy. Histochemistry and cytochemistry tests were performed to examine the chemical composition of exudates. Thin layer chromatography was used to determine the presence of alkaloids and terpenes in gynoecium and fruit extracts, and in fresh nectar stored in the nectar chamber.center dot Key Results Peltate trichomes at different developmental stages appear side by side from floral budding up to pre-dispersal fruit. Large plastids with an extensive internal membrane system consisting of tubules filled with lipophilic material, abundant smooth endoplasmic reticulum, few Golgi bodies, lipophilic deposits in the smooth endoplasmic reticulum and mitochondria, and scattered cytoplasmic oil droplets are the main characteristics of mature head cells. The secretion which accumulates in the subcuticular space stains positively for hydrophilic and lipophilic substances, with lipids prevailing for fully peltate trichomes. Histochemistry and thin layer chromatography detected terpenes and alkaloids. Fehling's test to detect of sugars in the secretion was negative.center dot Conclusions the continuous presence and activity of peltate trichomes on the ovary of Z. montana from early budding through to flowering and fruiting set, and its main chemical components, alkaloids and terpenes, suggest that they serve a protective function and are not related to the floral nectar source or to improving nectar quality.
Keywords: Bignoniaceae; cytochemistry; development; ovary; peltate trichomes; thin layer chromatography; ultrastructure; Zeyheria montana